Transfusion of leukoreduced blood products and risk of antibody‐mediated rejection of renal allografts. Issue 8 (1st September 2018) - Bynum, Jennifer P.; Zachary, Andrea; Ness, Paul M.; Luo, Xun; Bagnasco, Serena; King, Karen E.; Segev, Dorry L.; Orandi, Babak J.; Warren, Daniel S.; Fuller, Alice; Ciappi, Ana; Montgomery, Robert; et al.
Abstract : BACKGROUND: Antibody‐mediated rejection (AMR) is a major barrier to the long‐term function of renal allografts. White blood cells, which may be present in red blood cell (RBC) units, and platelets (PLTs) express HLA antigens that may increase the risk of AMR by inducing or increasing humoral sensitization to HLA. STUDY DESIGN AND METHODS: A retrospective cohort study of HLA‐incompatible (HLAi) renal transplant recipients between 2004 and 2015 was conducted. Data on apheresis PLT and leukoreduced RBC transfusions within 4 weeks of transplantation, demographic information, and biopsy‐proven AMR were collected from medical records and the Scientific Registry of Transplant Recipients. Patients were evaluated until they showed evidence of AMR or until 1 year posttransplant, whichever came first. Multivariable analysis with Cox modeling was performed. RESULTS: Of 244 individuals, 182 (74.6%) received RBCs and 20 (8.2%) of those also received PLTs. During the first year posttransplant, 97 (39.8%) had AMR. RBC‐alone or RBC and PLT transfusions were not associated with increased risk of AMR after adjustment for panel‐reactive antibody, years on dialysis, HLA antibody strength, and number of therapeutic plasma exchange treatments (adjusted hazard ratio [adjHR] 1.00, 95% confidence interval [95% CI] 0.59‐1.69; and adjHR 0.68, 95% CI 0.28‐1.68, respectively). For each 1‐unit increase in RBC transfusions, there was no association with AMR (adjHR 0.94, 95% CI 0.85‐1.05). Only HLA antibody strength before transplantation was associated with AMR (adjHR 2.23, 95% CI 1.10‐4.52; cytotoxic crossmatch compared to crossmatch negative but detectable donor‐specific HLA antibodies). CONCLUSIONS: Patients who receive an HLAi transplant who are transfused with leukoreduced RBCs or PLTs in the peritransplant period are at no higher risk of AMR than nontransfused patients.